Professional competencies of cultural managers and promoters - Sanlucar Estrada, Ramona Elizabeth (Emerging Trends in Education, 2024)
The cultural manager and promoter is a professional who is recently being formed in the Universidad Juárez Autónoma de Tabasco. With the purpose of assessing the achievement of the graduate profile, which is established in the official curriculum, research is conducted under a quantitative approach and the methodological design of evaluative research; with the purpose of generating an instrument that evaluates the competencies that make up the graduate profile of this professional, integrated with five specific competencies. Since cultural management is a discipline under construction, it was necessary, in the first stage of the research, to make a documentary review of the competencies construct, from the semantic conception and the sociocultural constructivist perspective. In a second stage, several analyses of the graduate profile; were carried out, and based on the results obtained, the conceptual, procedural, and attitudinal components that integrate them were identified, which will support the choice of the technique and formulation of the instrument with which it is expected to assess whether these are developed by the students and graduates of this profession.
Keywords: competencies; components; manager and promoter cultural; graduation profile